Minority Communities "Trapped" in Migration Waves in Vietnam: A Comparative Analysis within the Southeast Asian Context - Thu, Trang Nguyen (Philippine Social Science Journal, 2025)
Vietnam’s ethnic minorities face significant climate and poverty challenges that drive youth migration while leaving the elderly behind; yet, limited skills and geographic isolation entrap many, particularly within the country’s 14 smallest ethnic groups. This policy-descriptive study analyzed post-COVID-19 national data to assess these populations, examining how gender, age, and cultural barriers contribute to their economic immobility. Findings reveal extreme poverty disparities—notably an 89.3% impoverishment rate among the Chut people—alongside widespread health and occupational skill deficits. By drawing parallels with marginalized communities in the Philippines, the research underscores the limitations of uniform interventions in Southeast Asia. Consequently, it advocates for the National Target Program to adopt tailored, region-specific policies that address historical inequities and the specific demands of the modern digital economy.